Data-Driven Platform Encroachment - Chongwoo Choe; Antoine Dubus; Noriaki Matsushima; Shiva Shekhar (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Marketplace platforms are central players in online retail and are in an advantageous position to leverage data generated by third-party sellers.This paper analyzes how a platform's encroachment decision - whether to enter its marketplace as a direct competitor - is shaped by regulations that restrict its use of seller data. We show that the platform's encroachment decision follows a non-monotonic pattern: it enters against sellers with either relatively low or sufficiently high brand value, but remains a pure intermediary for intermediate brand values. The data ban regulation alters this strategy by making the platform more likely to exclude low brand-value sellers and more likely to accommodate high brand-value sellers. The implication is that, while such regulation can enhance competition in markets with high-value sellers, it can inadvertently harm sellers and reduce consumer surplus in emerging markets, where sellers typically lack brand recognition and depend on platform visibility. These results underscore the need for more nuanced regulatory approaches - promoting data sharing in emerging markets and targeted bans in mature, established markets - to better balance welfare and competition.
Keywords: L21; L51; L42; 330; marketplace platforms; data regulations; digital markets act; innovation